Dutch Parelsnoer Institute-Cerebrovascular Accident (CVA) Study: A Large Multicenter Clinical Biobank with Standardized Collection and Storage. (19th July 2018) - Van Os, H. J. A.; Ruigrok, Y. M.; Manniën, J.; Van Dijk, E. J.; Koudstaal, P. J.; Luijckx, G. J.; Nederkoorn, P. J.; Van Oostenbrugge, R. J.; Visser, M. C.; Kappelle, L. J.; Verspaget, H. W.; Algra, A.; et al.
The Dutch Parelsnoer Institute-Cerebrovascular accident (CVA) Study is part of the Parelsnoer Institute (PSI), initiated in 2007 by the Netherlands Federation of University Medical Centers (NFU). PSI is a cooperation of all eight Dutch University Medical Centers (UMCs) and aims at building large prospectively collected datasets with uniformly and standardized storage of biomaterials for complex diseases. Currently, PSI covers 18 disease-specific cohorts called 'Pearls', and this number is still growing. One of these cohorts is the Stroke or CVA Pearl. For each of the cohorts, PSI offers the UMCs an infrastructure and standard procedures for storing the specific biomaterials in their certified biobanks. Clinical data are stored in a central database after being pseudonymized to ensure patient privacy. For the Parelsnoer Institute-CVA Study, blood for genetic analysis, serum and plasma are collected according to nationally agreed standards. Currently (November 2017) the Stroke Pearl has stored blood samples with prospectively obtained clinical data of around 6000 patients in all UMCs combined. Blood samples and data are available for all researchers with a methodologically valid research proposal.